Analysis on the characteristics and causes of the "23·7" torrential rainfall event in North China - Shunan YANG; Fanghua ZHANG; Yi HU; Shuang CHEN; Wei ZHAO; Wenli HUA; Aixia FENG (暴雨灾害, 2023)
An historically heavy rainfall event occurred in North China from 29 July to 1 August in 2023, causing serious disasters. In this study, the precipitation characteristics and causes of this heavy rainfall event was investigated utilizing various observational data from such as conventional surface and upper air data, FY-4A satellite TBB, and ERA5 reanalysis data. The results are as follows. This event exhibited significant extremity in North China in terms of many aspects, such as the duration and accumulated precipitation. Torrential rainfall occurred in many regions, including western Beijing, central and southwest Hebei, with the total accumulated precipitation amount of exceeding 400 mm and even greater than 1 000 mm locally. The extreme precipitation was mostly distributed in the eastern foot of the Taihang Mountains. Based on the evolution characteristics of FY-4A satellite TBB, hourly precipitation, and major impact systems, severe precipitation can be divided into three stages. The first stage had the largest precipitation coverage and accumulated precipitation, while the second stage had the strongest convection with extreme hourly precipitation of over 100 mm·h-1 occurring at several stations. The extremely heavy rainfall event took place under the background of stable circulation with Typhoon residual vortex stagnating after its moving northward. Typhoons "Doksuri" and "Khanun" provided continuous and abundant water vapor and energy. Obvious upper-level divergence and low-level strong convergence provided stable and powerful dynamic conditions. Due to the forced uplift of the eastward airflow along the eastern foothills of the Taihang Mountains, precipitation was increased and sustained.